Beginning Oracle Application express - Greenwald, Rick (Wrox beginning guides., 2009)
Oracle Application Express is an easy-to-use application development environment built on the Oracle technology stack. There are two aspects of that previous sentence that you may find jarring--that Oracle, a company widely known for its database technology, has an application development environment, and that Oracle, a company thought of as delivering high-end, enterprise-ready technology, has anything that is easy to use. But, as this book will show, the introductory statement is completely accurate. Oracle Application Express, commonly known as Oracle APEX or simply APEX, does benefit from th.